Apoptotic Effects of Oryza Sativa L. Extract in Human Melanoma Cell - Poommarapan, Kanita; Tancharoen, Salunya; Leenutaphong, Petchpailin; Srichan, Ratchaporn; Nararatwanchai, Thamthiwat; Rummaneethorn, Paisal (Journal of The Department of Medical Services, 2024)
Background: Malignant melanoma, originating from melanocytes, is the most dangerous type of skin cancer. Melanoma treatment includes surgery and the combination of surgery and chemotherapy, immunotherapy, targeted therapy and radiation therapy due to stage of melanoma. Oryza sativa Linn (OS) is a type of black rice found in various regions across Southeast Asia. The main bioactive components of OS extracts are anthocyanins, which have anti-tumor effects. Objective: In this study, we conducted cell viability, the cell cycle, and apoptosis analysis of a human melanoma A375 cells following treatment with OS extract. Methods: The effects of different OS concentrations treatment on human melanoma A375, cell cycle, and apoptosis were assessed by Flow cytometry. The identity of the protein was confirmed through SDS-PAGE and Western blotting. Results: We demonstrated from cell cytotoxicity assay that OS decreases cells viability after OS treatment at concentration 1.25, 2.5, 5 and 10 mg/ml. Flow cytometry showed that OS extract concentration at 2.5 mg/ml induces A375 cell cycle arrest at S phase and 5 and 10 mg/ml OS induces sub-G1 cell cycle arrest. OS extract concentration 2.5, 5 and 10 mg/ml induced A375 cell apoptosis. Apoptosis induction was accompanied by up-regulation caspase-8 and p53 expression. Conclusion: Our data show that the OS disrupted melanoma cell proliferation and induced apoptosis.